FoxG1 Interacts with Bmi1 to Regulate Self‐Renewal and Tumorigenicity of Medulloblastoma Stem Cells123. (5th July 2013) - Manoranjan, Branavan; Wang, Xin; Hallett, Robin M.; Venugopal, Chitra; Mack, Stephen C.; McFarlane, Nicole; Nolte, Sara M.; Scheinemann, Katrin; Gunnarsson, Thorsteinn; Hassell, John A.; Taylor, Michael D.; Lee, Cathy; et al.
Abstract Brain tumors represent the leading cause of childhood cancer mortality, of which medulloblastoma (MB) is the most frequent malignant tumor. Recent studies have demonstrated the presence of several MB molecular subgroups, each distinct in terms of prognosis and predicted therapeutic response. Groups 1 and 2 are characterized by relatively good clinical outcomes and activation of the Wnt and Shh pathways, respectively. In contrast, groups 3 and 4 ("non‐Shh/Wnt MBs") are distinguished by metastatic disease, poor patient outcome, and lack a molecular pathway phenotype. Current gene expression platforms have not detected brain tumor‐initiating cell (BTIC) self‐renewal genes in groups 3 and 4 MBs as BTICs typically comprise a minority of tumor cells and may therefore go undetected on bulk tumor analyses. Since increasing BTIC frequency has been associated with increasing tumor aggressiveness and poor patient outcome, we investigated the subgroup‐specific gene expression profile of candidate stem cell genes within 251 primary human MBs from four nonoverlapping MB transcriptional databases (Amsterdam, Memphis, Toronto, Boston) and 74 NanoString‐subgrouped MBs (Vancouver). We assessed the functional relevance of two genes, FoxG1 and Bmi1, which were significantly enriched in non‐Shh/Wnt MBs and showed these genes to mediate MB stem cell self‐renewal and tumor initiation in mice. We also identified their transcriptional regulation through reciprocal promoter occupancy in CD15+ MB stem cells. Our work demonstrates the application of stem cell data gathered from genomic platforms to guide functional BTIC assays, which may then be used to develop novel BTIC self‐renewal mechanisms amenable to therapeutic targeting. STEM Cells2013;31:1266–1277